Financing Solutions to Reduce Natural Gas Flaring and Methane Emissions - Lorenzato, Gianni (Washington, DC: World Bank, 2022)
Global oil and gas emissions fell to historic lows in 2020 as a result of the decline in global demand associated with the COVID-19 (Coronavirus) pandemic. Data released by the International Energy Agency suggest that CO2 emissions are on the rise as energy demands increase after the pandemic. Whether emissions will rebound to precrisis levels largely depends on governments’ emphasis on clean energy transition in their efforts to reboot economic growth. In 2019, direct and indirect emissions from the oil and gas sector represented about 15 percent of the global energy sector’s greenhouse gas emissions. More than half of these emissions came from flaring and methane released during oil and gas operations.